Monetary policy transmission with two exchange rates and a single currency: The Chinese experience - He Qing; Iikka Korhonen; Qian Zongxin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
In emerging market economies, transmission of monetary policy through the foreign exchange market is complicated by the coexistence of financial restrictions and arbitrages. Using China as an example, we show that the coexistence of exchange rate interventions, capital controls and an on-shore-offshore exchange rate differential makes the long run equilibrium in the currency market nonlinear. Disturbances to this nonlinear long run equilibrium could offset the impact of monetary policy actions on domestic price stability. Omitting such nonlinearity leads to biased inference on the effectiveness of monetary policy.
URN:NBN:fi:bof-201710231647
Keywords: E52; F31; F40; 330